A Novel Sampling Approach in GNSS-RO Receivers with Open Loop Tracking Method - leila mohammady (AUT Journal of Electrical Engineering, 2019)
Propagation of radio occultation (RO) signals through the lower troposphere results in high phase acceleration and low signal to noise ratio signal. The excess Doppler estimation accuracy in lower troposphere is very important in receiving RO signals which can be estimated by sliding window spectral analysis. To do this, various frequency estimation methods such as MUSIC and ESPRIT can be adopted. Due to the cost and bandwidth constraints, reducing the sampling rate at GNSS receivers of LEO satellite is necessary which causes aliasing. A method of resolving frequency ambiguities is the simultaneous sampling of signal by multiple sample frequencies (MSF). Accordingly, we study the capacity of MSF method to improve the spectral efficiency and use accurate frequency estimation schemes to enhance the excess Doppler estimation accuracy of RO signal in post-processing. Via simulation results, the accuracy of excess Doppler estimation in post-processing based on both single sample frequency (SSF) and MSF methods for different frequency estimation methods are compared. Simulation results reveal that the MSF method has better performance than that of the SSF method. Besides, it is shown that Jacobsen and Jacobsen with Bias methods almost have the same performance and their estimation error is less than that of other methods. By exploiting the proposed scheme, the frequency estimation error is significantly decreased and it is negligible compared to the traditional methods. Moreover, by using this scheme, we have 41.6%